Model ARIMA untuk Peramalan Harga Beras di Kabupaten Ogan Komering Ilir Provinsi Sumatera Selatan - Endang Lastinawati; Andy Mulyana; Imron Zahri; Sriati Sriati (Seminar Nasional Lahan Suboptimal, 2019)
Lastinawati E, Mulyana A, Zahri I, Sriati S. 2019. ARIMA model for rice price forecasting in Ogan Komering Ilir Regency, South Sumatra Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 192-200. Palembang: Unsri Press. The price of a commodity is a very important factor that influences the decisions of producers in production activities, and consumers in their consumption activities. This study aims to build an ARIMA model for forecasting rice prices based on the quality of premium and medium rice. The study was carried out in Ogan Komering Ilir Regency as the center of swamp rice production in the South Sumatra Province. The ARIMA model of rice price was built using the Box Jenkins method with sequential data on weekly rice prices since the second week of March 2016 to the second week of September 2018. The results showed that the best model for the retail price of premium rice was ARIMA (8,1,0), whereas for medium rice retail prices, ARIMA (4,1,1) is obtained. The forecasting results show that the price of premium and medium rice in OKI Regency until December 2020 continues to increase.Keywords: ARIMA model, premium and medium rice, retail price